Accessory scrotum and congenital perineal lipoma in a child with type-2 congenital pulmonary airway malformation (CPAM): A report of an unusual - Fathaddin, Amany A. (International Journal of Health Sciences, 2018)
Accessory scrotum and congenital perineal lipoma are unusual congenital anomalies. Congenital pulmonary airway malformation (CPAM) is a rare congenital disorder of the lung. There are five types of CPAM, each with a different clinical presentation and prognosis. The present report involves a case of type 2 CPAM associated with accessory scrotum and congenital perianal lipoma.